Insights into Alternaria in apple fruit causing mouldy core, external infection and mycotoxin production under retail and storage conditions - Pavicich, María Agustina; Maldonado, María Luisa; Nguyen, Truong Nhat; De Boevre, Marthe; De Saeger, Sarah; Patriarca, Andrea (Elsevier, 2025)
Apple fruit is widely consumed worldwide, but fungal contamination in the postharvest stage presents a significant food safety concern. This study evaluates the production and accumulation of Alternaria mycotoxins, including alternariol (AOH), alternariol monomethyl-ether (AME), and the modified forms (AOH-3-S, AME-3-S, AOH-3-G, AME-3-G), altenuene (ALT), tenuazonic acid (TeA), tentoxin (TEN), altertoxin I and II (ATX[sbnd]I, ATX-II), in Red Delicious apples under simulated retail and post-harvest conditions. Three Alternaria tenuissima strains (isolates 02, 31 and 36) were inoculated in apple fruit at two sites separately (core and exterior) and incubated at two temperatures (25 °C and 4 °C) for 1 and 9 months. Mycotoxin production was quantified using LC-MS/MS, revealing significant variability across strains and conditions. Isolates 02 and 36 exhibited significant temperature and site-dependent variability in mycotoxin production. Higher levels of AOH, AME, ALT, and ATX-I were produced at 25 °C and in the core. Long-term cold storage delayed fungal growth but did not prevent mycotoxin accumulation, raising concerns about the safety of processed apple products. These findings highlight the need for stricter monitoring of mycotoxins during post-harvest storage to mitigate health risks. The findings provide insights into their toxigenic capacity in vivo and highlight potential risks for food safety.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; 3008 Horticultural Production; Infectious Diseases; 2.2 Factors relating to the physical environment; Food safety; Mycotoxins; Pome fruit; Postharvest; Storage; Microbiology